Modeling for surface roughness in end-milling of titanium alloy Ti-6AI-4V using uncoated WC-Co and PCD Inserts - Ginta, Turnad Lenggo; Amin, A. K. M. Nurul; Karim, A.N. Mustafizul; Ishtiyaq, M. H. (2007)
This paper presents an approach to optimize the surface finish in end milling titanium-alloy of Ti-6AI-4V using uncoated WC-Co and PCD inserts under dry conditions. Response surface methodology is utilized to develop an efficient mathematical model for surface roughness in terms of cutting speed, feed and axial depth of cut. For this purpose, a number of machining experiments based on factorial design of experiments method are carried out in order to determine surface roughness values. The 3FI surface roughness models have been developed at 95% confidence interval for both the inserts. The adequacy of the models has been verified by analyzing the variance.